Towards all optical DCI networks - Khanna, Ginni; Zhu, Shengxiang; Filer, Mark; Gkantsidis, Christos; Parmigiani, Francesca; Karagiannis, Thomas (Optical Fiber Communication Conference (OFC'20), 2020)
We propose and experimentally demonstrate an all-optical architecture for data center interconnect networks with reconfiguration times of a few seconds. Filtering and amplification transient effects have minimal impact on BER performance.